3-D spatial memory and navigation: functions and disorders. Issue 1 (February 2017) - Brandt, Thomas; Zwergal, Andreas; Glasauer, Stefan
Abstract : Purpose of review: The aim of this review is to report on the specialized neuronal systems mediating spatial orientation and navigation discovered in animal experiments. These findings have important implications for the clinical management of patients with vestibular disorders or dementia and for translational research in these fields. Recent findings: The following anatomically and functionally separate, but nevertheless cooperative cell types have been characterized: angular head velocity cells and head direction cells, which depend on vestibular input and interact with place cells and grid cells, which represent position and distance. The entire system is thought to encode internal cognitive maps whose spatial data can be utilized for navigation and orientation. Flying and swimming species use spatial orientation and navigation isotropically, i.e., in the earth-horizontal and vertical directions, whereas ground-based species, including humans, perform better in the earth-horizontal plane (anisotropically). Examples of clinical disorders with deficits of spatial orientation and navigation are bilateral peripheral vestibulopathy, mild cognitive impairment, and dementia. Summary: Testing spatial orientation and navigation should become an integral part of routine neurological examinations, especially in the elderly. Also desirable are the further development and standardization of simple and reliable smart phone-based bedside tests to measure these functions in patients.